Rethinking, Returning, Repossessing. (3rd May 2020) - Bui, Long T.
ABSTRACT: Exhuming the legacy of a state that exists only in apparition and in the flesh, I study the footprints of diasporic youth migrating back to Vietnam, intergenerational hostility among kin, soldiers battling the demons of "future Vietnams, " and feminists and queers fighting for sanctuary within "Little Saigon." I rethink how heteropatriarchy and patriotic hypermasculinity produced the gendered sexual violence that recurs in the name of community.